EVALUASI SISTEM PENGENDALIAN INTERNAL TERHADAP PIUTANG USAHA PADA PT. TELEKOMUNIKASI INDONESIA, Tbk WITEL JATIM SELATAN (MALANG) - Ervin Permatasari; Adri Putra Nugraha (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
The objective of this research is to determine and evaluate the internal control system of the accounts receivables at PT. Telekomunikasi Indonesia, Tbk Witel Jatim Selatan (Malang). This research used qualitative descriptive method with a case study approach. The data in this research is obtained through observation, interviews, and documentation. The result of this research shows that the system of internal control over accounts receivables at Telekomunikasi Indonesia, Tbk Witel Jatim Selatan (Malang) already works quite effectively, where the management of company has implemented the basic concepts and principles of internal control by COSO, however still needs some improvement. Improvements need to be conducted on the company policy to establish customers assurance and documentation of the Standard Operating Procedure (SOP). Keywords: Internal Control Systems, Accounts Receivables, COSO